Analytical approach for vertical floor acceleration of regular RC frames under earthquake excitation. (15th January 2022) - Xiang, Yang; Guo, Jia; Kishiki, Shoichi
Highlights: Dynamic substitution of floor slabs and slab-frame integrations. Analytical model and approach for vertical floor acceleration (VFA) of RC frames. VFA can be estimated via the response spectral method. Validation via response history analyses conducted on finite element models. Abstract: Vertical floor acceleration (VFA) analysis arises as an important issue for seismic design of floor-attached nonstructural components (e.g., ceilings). However, to date, estimating the VFA is hardly accessible in the literature. In this paper, an analytical method is proposed for the VFA of regular RC frames. Here "regular" means the frame has uniform spans along each principal direction, so the structure can be represented by a single-span analogy. Firstly, the fundamental frequency, modal mass, and modal participation factor of a clamped floor slab are analyzed based on the classic thin-plate theory. Then, the dynamic properties of the clamped floor slab are adjusted to account for the effect of the flexible beam restraints (non-clamped). According to the adjusted dynamic parameters, the beam-restrained slab is substituted by a single-degree-of-freedom system, and is assembled with the column-beam system to form the global dynamic model for the structure. Based on the assembled model, the analytical process for the VFA is presented. The feasibility of the model is validated using the finite element modelling (FEM) method. The vertical dynamic properties and the peak VFA of a single-, 3-, 6-, and 9-story frame are computed using the FEM and the proposed analytical approach. Results show that the VFA obtained from the analytical approach is close to the FEM outcomes. Furthermore, important features of VFA are revealed by the computation. It is shown that the VFA could be 10 times as large as the peak vertical ground acceleration. A larger VFA appears at the higher stories, yet the relationship between the VFA and the height is nonlinear because of the effects of the higher-order modes.